2008
DOI: 10.1007/s11571-008-9050-4
|View full text |Cite
|
Sign up to set email alerts
|

Sensory gating and its modulation by cannabinoids: electrophysiological, computational and mathematical analysis

Abstract: Gating of sensory information can be assessed using an auditory conditioning-test paradigm which measures the reduction in the auditory evoked response to a test stimulus following an initial conditioning stimulus. Recording brainwaves from specific areas of the brain using multiple electrodes is helpful in the study of the neurobiology of sensory gating. In this paper, we use such technology to investigate the role of cannabinoids in sensory gating in the CA3 region of the rat hippocampus. Our experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
2
11
1
Order By: Relevance
“…Such a contention could explain the lack of significant differences between controls and cannabis users in the study by Quednow et al (2004) which used an uninstructed PPI task. A number of recent studies have shown that sensory gating of the P50 response (a psychophysiological measure that has been likened to PPI) is disrupted by administration of cannabinoids in humans (Rentzch et al 2007) and in rats (Hajos et al 2008;Zachariou et al 2008), suggesting that cannabinoids disrupt early information processing or gating. However, drug conditions may have differing effects on PPI and P50 gating (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Such a contention could explain the lack of significant differences between controls and cannabis users in the study by Quednow et al (2004) which used an uninstructed PPI task. A number of recent studies have shown that sensory gating of the P50 response (a psychophysiological measure that has been likened to PPI) is disrupted by administration of cannabinoids in humans (Rentzch et al 2007) and in rats (Hajos et al 2008;Zachariou et al 2008), suggesting that cannabinoids disrupt early information processing or gating. However, drug conditions may have differing effects on PPI and P50 gating (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of natural extensions to neural field models to incorporate ever more biological realism, including the incorporation of slow intrinsic currents that underlie bursting behaviour in single neurons [86,11], synaptic depression and adaptation [87], dendritic processing [61], neuromodulation, say by endo-cannabinoids [88], and anaesthetic drug action [66,89,68,90]. Moreover, it is possible to gener-alise such models even further to treat feature selectivity such as that observed in visual cortex for orientation [10], spatial frequency [91] and texture [92].…”
Section: Tissue Modelsmentioning
confidence: 99%
“…This wave, known as N40, is considered a homolog to the P50 wave recorded in humans (Adler et al 1986). The cannabinoid agonist WIN55,212-2 disrupts auditory gating in rats, in the hippocampus (CA3, dentate gyrus) and the medial prefrontal cortex (mPFC), and this disruption is prevented by the CB 1 antagonist SR141716A Zachariou et al 2008). The CB 1 agonist CP-55940 has been reported not only to impair PPI in rats but also auditory gating and neuronal synchrony in limbic areas such as the hippocampus and entorhinal cortex, as evaluated through theta field potential oscillations (Hajós et al 2008).…”
Section: Disturbances Of the Endocannabinoid System In Schizophreniamentioning
confidence: 99%